Investigation of Teachers’ Self Efficieny of Educational Game Teaching: Case of Alanya - Mehmet Arslan; Meriç Ödemiş (Türk Spor ve Egzersiz Dergisi)
In this study, it was aimed (i) to compare teachers' educational game playing self-efficacy in terms of gender, age, marital status, educational status, seniority, different branches and (ii) to examine educational game playing self-efficacy levels. General survey method was used in the research. The sample group of the study consisted of 50 physical education and sports, 50 preschool and 50 classroom teachers, totalling 150 teachers working in Alanya district. In data collection, the 'Educational Play Self-Efficacy Scale' developed by Altınkök and Yılmaz (2018) and the demographic information form were applied online via Google® forms to the individuals who voluntarily participated in the study. The data obtained from the study were analysed using IBM SPSS 25.0 statistical package programme. Since the data showed normal distribution as a result of the kurtosis and skewness test, Independent T test was used for binary variables and One Way Anova test was used for three or more variables. As a result of the findings, it was determined that there was a significant difference in the participants' educational game playing competences in terms of age, seniority and branch variables. However, no significant difference was found in terms of gender and educational status variables. In addition, while physical education and sports teachers' self-efficacy in playing educational games is better than other branch teachers, pre-school teachers' efficacy levels in the application dimension are lower than other branches. It was determined that teachers' self-efficacy for playing educational games was at a high level, but there were differences in their self-efficacy for playing educational games in terms of some variables.